Rethinking the Fifth Empire: António Vieira and the Clavis Prophetarum - Valdez,Maria Ana T. (2012)
It is this papers purpose to introduce António Vieiras model of the Fifth Empire and to contextualize it within the biblical exegesis tendencies of his time. Vieiras conceptualization is of utmost importance for understanding the intellectual and religious environment of seventeenth-century Portugal: a disturbed time, during which people searched for answers in biblical prophecies to explain the reasons behind so much suffering. Vieiras systematization, however, was first viewed as a possible heresy by the Portuguese Inquisition and was only later, and in part, rehabilitated by Antonio Casnedi. The Clavis prophetarum is also an expression of an eschatological hope common to the Iberian world, although it focuses mostly on Portugal.